The Influence of Capital Expenditure, Nickel Exports, Nickel Prices, and Return on Equity on Stock Prices of Nickel Mining Companies in Indonesia - Lesmana, Angga Setia; Defung, F; Jamaluddin, Jamaluddin (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to investigate the effect of Capital Expenditure, Nickel Exports, Nickel Prices, and Return on Equity on Stock Prices of Nickel Mining Companies in Indonesia during the period of 2014-2023. The research design uses a causal approach. The population of this study is nickel mining companies in Indonesia that are registered by the Indonesia Stock Exchange throughout the research period, 2014-2023, with the total population of 8 companies. This study uses saturation sampling method. There are 8 companies as samples of this study, resulting in 66 financial report data. The data is analyzed using the multiple regression. The research findings indicate that capital expenditure has a significant and positive effect on the stock price of nickel mining companies (Significance value is 0.000 <α = 0.05). Nickel exports do not affect the stock price of nickel mining companies (Significance value is 0.064 > α = 0.05). Nickel prices do not affect the stock price of nickel mining companies (Significance value is 0.311 > α = 0.05). Return on Equity has a significant and positive effect on the stock price of nickel mining companies (Significance value is 0.015 <α = 0.05).